The Utilization of Betel Chewing Ingredients (Nginang) As an Alternative Dye in Microscopic Slide of Stem Tissues - DINAR SUKMA NIRMALA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2017)
Biological concepts not only delivered theoretically, but also practically. One of them is microscopic slide. The damaged of microscopic slide is often caused by the lack of dye visibility. This damage can be solved by making new microscopic slide to support the biological learning using coloring materials which are easier to search, for example the dyes of chewing material. The study aimed to make microscopic slide with alternative dyes from chewing materials and to describe the feasibility of plant tissue preparations with the alternative dyes of betel chewing ingredients. This study involved the development of alternative dyes. There were three stages in this study, namely the manufacture of alternative dyes from betel chewing ingredients, making microscopic slide with paraffin method. Validation of the slide involved the relevancy between slide and the subject material, effectivity and absorption of the slides. The results of this research produced 12 of preparation incision transverse of the stem from 4 kinds of specimen (sirih belanda/Scindapsus aureus, keladi dua warna/Caladium bicolor, kamboja merah/Adenium obesum, kembang sepatu/Hibiscus rosa-sinensis). This study revealed that betel chewing ingredients is worth used to support observation criteria very reasonable with the percentage 88%-99%. Keywords: Development of Dyes, Microscopic Slide, Paraffin Methods, Alternative Dye, Betel Chewing Ingredients